Evolución de las condiciones de vida en el sector rural de Medellín, de acuerdo a los indicadores de calidad de vida (2011)
ABSTRACT: The Indicador de Calidad de Vida en rural zone shows an increase: From a Global ICV of 74,29 in the 2009 to 76,78 in the 2010. All the Corregimientos tend to improve their quality of life. The majors increases appear in Santa Elena and San Cristóbal. The group of Corregimientos with smaller increase was AltaVista. The group of Corregimientos with smaller quality of life continues being Palmitas, followed of AltaVista. The group of Corregimientos with better quality of life is San Antonio de Prado, followed by Santa Elena.